Modified Protocol to Enable the Study of Hemorrhage and Hematoma in a Traumatic Brain Injury Mouse Model - Joo, Hyejin; Bae, Jinhyun; Park, Jae-Woo; Lee, Beom-Joon; Lee, Byoung Dae; Bu, Youngmin (Frontiers in Neurology, 2021)
To date, many studies using the controlled cortical impact (CCI) mouse model of traumatic brain injury (TBI) have presented results without presenting the pathophysiology of the injury-core itself or the temporal features of hemorrhage (Hrr). This might be owing to the removal of the injury-core during the histological procedure. We therefore developed a modified protocol to preserve the injury-core. The heads of mice were obtained after perfusion and post-fixed. The brains were then harvested, retaining the ipsilateral skull bone; these were post-fixed again and sliced using a cryocut. To validate the utility of the procedure, the temporal pattern of Hrr depending on the impacting depth was analyzed. CCI–TBI was induced at the following depths: 1.5 mm (mild Hrr), 2.5 mm (moderate Hrr), and 3.5 mm (severe Hrr). A pharmacological study was also conducted using hemodynamic agents such as warfarin (2 mg/kg) and coagulation factor VIIa (Coa-VIIa, 1 mg/kg). The current protocol enabled the visual observation of the Hrr until 7 days. Hrr peaked at 1–3 days and then decreased to the normal range on the 7th day. It expanded from the affected cortex (mild) to the periphery of the hippocampus (moderate) and the brain ventricle (severe). Pharmacological studies showed that warfarin pretreatment produced a massively increased Hrr, concurrent with the highest mortality rate and brain injury. Coa-VIIa reduced the side effects of warfarin. Therefore, these results suggest that the current method might be suitable to conduct studies on hemorrhage, hematoma, and the injury-core in experiments using the CCI–TBI mouse model.